Lithuania's integration into Europe: Alternatives and choices - Vitkus, Gediminas (Politologija, 2025)
In the beginning of the article, the author postulates: "Lithuania's belonging to Europe is unquestionable". Thus, the main prospects for satisfying the national interests - namely, national security, economic welfare of the citizens, and maintenance of national identity - of Lithuania are tightly bound with the appertainance and further integration into the aforementioned area. However, G. Vitkus notifies, that in spite of the expressed wish of Lithuania saying that the country seeks entrance into European political, economic, and security organisations, in 1997, and particularly in summer 1997 in Madrid and in December in Luxembourg, it has finally become apparent that the delineated goals are not to be implemented easily. Nevertheless, the author claims that such a make-up of events is not to be viewed as a defeat. He says: "Postponement of the EU perspective, on the one hand, and ambiguity of the NATO perspective, on the other, have not only provided us with a chance to re-contemplate the vitality of our strategic choice, but has made us alert that Lithuania's integration into Europe cannot limit and confine itself to integration into these two structures. Moreover, NATO and the EU membership ought to be taken not so much as goals but as a means in order to achieve higher goals - the implementation of Lithuania's national interests." The author argues that Lithuania, which pursues the goals of deepening integration with Europe, intensifying its security, and managing the economic welfare of the citizens, must take advantage of "all the remaining" opportunities the contemporary situation sets forth. Thus, in this article, Gediminas Vitkus analyses these opportunities in detail.In the first section, "The integration of Lithuania into Europe and the national security," the author aims at discussing the alternative opportunities for attesting Lithuania's national security. With respect to NATO, the main possible guarantor of security, the author enumerates three main obstacles which vex this "hardly believable" - however strategic - entrance into NATO. According to G. Vitkus, the main of these is the geopolitical location of Lithuania. Further on, by reason of these obstacles, the author propounds five alternative opportunities to NATO. The most viable of these are the first three: first, further participation in the Partnership for Peace with NATO and the non-NATO states; second, membership in the EU; and third, regional co-operation with the Nordic and the Baltic States. The remaining two, Polish and Lithuanian strategic partnership and the lobby activities in Russia, in the author's opinion, can contend with neither membership in NATO nor participation in the North-Baltic security community. G. Vitkus emphasises that both intense and intimate partnership and co-operation with Poland and a lobby in Russia ought not to be abandoned and, especially Poland, should be viewed as a possible precious factor in intensifying Lithuania's security. Having discussed the character of these five propositions, the author proceeds, "as to remember," the nature of Lithuania's relations with Russia and the other CIS (Commonwealth of Independent States) countries. The author argues "that it is Russia's instability and the possible emergence of the revanchist power groups in the government which serve the role of the chief threat to Lithuania's and the region's security". In brief, G. Vitkus concludes the following: "as we may have seen, in the contemporary international situation, in Lithuania and on the regional level, there appear quite a number of tendencies which seem positive to Lithuania's overall security."The next section deals with an aspect of economic integration and the economic welfare of the state. The author claims that "the integration of Lithuania into the European economic realm is primarily related with its membership in the European Union". However, according to the author, these wishes were overturned by the European Commission in July 1997. Although the opinion of the European Commission deliberating whether to start negotiations with the applicant countries could be influenced by political considerations and the internal problems of the EU, it nevertheless can be stated that the opinion of the Commission concerning the rank of Lithuanian economy is fundamental enough. Therefore, with respect to membership in the EU, the author discusses the problem of economic costs and the benefits of this membership. Before proceeding to the table where arguments "pro" and "contra" of economic integration are enumerated, the author discusses the pillars and goals of intra-EU economic integration and common politics (e.g., agricultural, structural policy) which have been attained by the EU member-states so far.In conclusion, the author postulates that "the fact that Lithuanian government 'thirsts' for the membership in the EU not so much due to economic, but political, reasons, is very detrimental. At the first sight, it may seem that several Lithuanian politicians have not yet understood the full complexity of the problem. But this is what the author points with respect to Lithuanian political realities. In general, from security and economic perspective, there are no alternatives to Lithuania's membership in the EU, membership which would not only correspond to demands for guaranteeing the national security. From the standpoint of long-term economic development and state modernisation, this would be a progressive step as well. At last, the author advises: "Before passing the decision, it is essential to first identify and, from the economic standpoint, analyse different pre-access strategies and alternative tactics. Only this would help avoid the above-mentioned tendencies when the pre-access preparation was nearly becoming a technic-bureaucratic demand, but would first of all reflect the demands of the national economic development."
Keywords: -